As trajetórias laborais das trabalhadoras da Casa da Mulher Brasileira – Ceará: “Eu encaro como uma missão de trabalhar o empoderamento das mulheres” - Silva, Gabriela Freitas da (2023)
Work has a social function, potential, and subjective aspects that make it central in individuals' lives. Regarding women, work has specific characteristics that point to very different reverberations throughout their lives. The research conducted was linked to Social Psychology of Work (SPW) and analyzed the work trajectories of female workers at the Brazilian Women's House - Ceará (CMB). The space provides specialized and comprehensive care for women experiencing domestic and family violence, as well as activities that promote debate on the topic. By linking the category of experience to work trajectory, this research raised individual aspects related to the decision to work at CMB, sought to understand experiences related to violence, and describe the course of workers' work experiences. The research conducted is qualitative, using semi-structured interviews and the analysis process based on the Meaning Nucleus. Diverse work trajectories were identified, highlighting the workers' participation in social movements, the presence of a strong subjective commitment to the topic, distinct experiences with violence in their lives, and plural trajectories. The research also signaled characteristics specific to the "type of work" performed in the facility, a topic that can be further explored by other studies.